Bacillus thuringiensis and Its Pesticidal Crystal Proteins - Schnepf, E. (American Society for Microbiology, 1998)
During the past decade the pesticidal bacterium Bacillus thuringiensis has been the subject of intensive research. These efforts have yielded considerable data about the complex relationships between the structure, mechanism of action, and genetics of the organism’s pesticidal crystal proteins, and a coherent picture of these relationships is beginning to emerge. Other studies have focused on the ecological role of the B. thuringiensis crystal proteins, their performance in agricultural and other natural settings, and the evolution of resistance mechanisms in target pests. Armed with this knowledge base and with the tools of modern biotechnology, researchers are now reporting promising results in engineering more-useful toxins and formulations, in creating transgenic plants that express pesticidal activity, and in constructing integrated management strategies to insure that these products are utilized with maximum efficiency and benefit.